Formulasi Strategi Perbaikan Kinerja Perusahaan Properti Pasca Akuisisi (Studi Kasus: PT XYZ) - Mufrad Azmadahadid; Lukman M Baga; Setiadi Djohar (Jurnal Manajemen dan Organisasi, 2019)
PT XYZ is one of property companies that involved in apartment and condotel business in Yogyakarta. At present, PT XYZ had decreased in revenue due to decreased in unit sales and delinquent payments by existing customers. These problems made the company’s performance decrease so the company sold 38 percent of its shares to PT ADP and PT TBR. Together with the new management composition, the company strives to improve its performance. Therefore, a strategy formulation is needed to make the company performance being improved again. Interviews were conducted with informants selected by purposive sampling to identify company’s internal and external strategic issues. The IFE matrix (Internal Factor Evaluation) and EFE matrix (External Factor Evaluation) are used to evaluate company’s internal and external conditions. SWOT matrix (Strength, Weaknesses, Opportunities, and Threat) is used to find alternative strategies to improve company performance. There are five alternative strategies to improve company performance after acquisition, namely: (1) rebranding the names of apartments and condotels; (2) increase promotion and sales activities; (3) improve good relationship with consumers; (4) make value added for the apartments; (5) recruiting experienced sales employees.